Strategies for the improvement of the organizational culture of General Analytical Services S.A.C. applying the Denison model - Balcazar Guerra, Carmen (2018)
The problem presented in this research was divided into the 4 dimensions according to Denison's model for the measurement of the organizational culture of the laboratory services company Servicios Analíticos Generales S.A.C. When the questionnaire is applied according to the dimensions, it is seen that it is necessary to use strategies to improve the organizational culture.For applying the leadership and motivation strategies, the change in the organizational culture is appreciated, allowing the operations personnel to be integrated into the administrative.